EXPERIMENTAL STUDY OF CLINOPYROXENITE PARTIAL MELTING AND THE ORIGIN OF ULTRA-CALCIC MELT INCLUSIONS - Kogiso T.; Hirschmann M.M. (My University, 2001)
Ultra-calcic melt inclusions (UCMI: CaO>13.5 wt% and/or CaO/Al2O3>0.9) are magnesian and near-primary liquids trapped in volcanic phenocrysts from mid-ocean ridges, arcs, back-arcs, and ocean islands. UCMI can be subdivided into two classes based on tectonic association and degree of silica saturation: those from arcs are nepheline normative and those from all other localities (silicic UCMI) are hypersthene normative. Silicic UCMI share a number of common features, including primitive host minerals, low alkali contents, and variable ratios of K2O/TiO2 ranging to high values. Their compositions are not easily derived by partial melting of mantle lherzolite. Accordingly, we have performed a series of partial melting experiments on three clinopyroxenite compositions at 1.0 to 2.0 GPa to investigate the role of partial melting of clinopyroxene-rich lithologies in silicic UCMI genesis. Estimated solidus temperatures for all three compositions are similar to those of normal peridotites, but 1.0 GPa isobaric melt productivities are higher for clinopyroxenite than for peridotite. High degree partial melts of the clinopyroxenites are ultra-calcic and have similarities to silicic UCMI, but the experiments produce ultra-calcic liquids only at melt fractions greater than 30% and temperatures higher than 1,350 C at 1.0 GPa. Such temperatures are higher than those likely to be prevailing beneath normal mid-ocean ridges, which suggests that some or all silicic UCMI may originate by a process other than simple partial melting of clinopyroxene-rich lithologies. We consider a possible role for partial melting of depleted harzburgite in the genesis of silicic UCMI.